2008
DOI: 10.1152/jn.00625.2007
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Decrease in Short-Term Facilitation at Schaffer Collateral Synapses in Hippocampus Is mGluR1 Sensitive

Abstract: Speed HE, Dobrunz LE. Developmental decrease in short-term facilitation at Schaffer collateral synapses in hippocampus is mGluR1 sensitive. J Neurophysiol 99: 799 -813, 2008. First published November 21, 2007 doi:10.1152/jn.00625.2007. Developmental changes can occur in the dynamic properties of synapses, known as short-term plasticity. Using rat acute hippocampal slices at room temperature, we have previously shown a decrease in short-term facilitation at Schaffer collateral synapses from young adults compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 74 publications
3
32
1
Order By: Relevance
“…# P \ 0.05 indicated the difference between P16-P19 and P20-P23 in a and asterisks mark significant differences between the two groups linked by line in b, c, * P \ 0.05 or P \ 0.01 (n = 28) group, the significant changes appeared from P12-P15 (n = 18) to P16-P19 group together with from P16-P19 to P20-P23 group (Fig. 4a one-way ANOVA and Post Hoc test, P \ 0.05), which was in accordance with research by Speed and Dobrunz (2008) in hippocampus. In addition, we further took a comparison among the fitted line of STP at last three development stages with F-test (P20-P23, P24-P27, and P [ 27 groups), it was showed that the short-term facilitation induced by the 5-pulse stimulations in P [ 27 group significantly weakened compared with that in P20-P23 group (F-test, P \ 0.05).…”
Section: Developmental Changes Of Stimulus-evoked Excitatory Postsynasupporting
confidence: 88%
See 1 more Smart Citation
“…# P \ 0.05 indicated the difference between P16-P19 and P20-P23 in a and asterisks mark significant differences between the two groups linked by line in b, c, * P \ 0.05 or P \ 0.01 (n = 28) group, the significant changes appeared from P12-P15 (n = 18) to P16-P19 group together with from P16-P19 to P20-P23 group (Fig. 4a one-way ANOVA and Post Hoc test, P \ 0.05), which was in accordance with research by Speed and Dobrunz (2008) in hippocampus. In addition, we further took a comparison among the fitted line of STP at last three development stages with F-test (P20-P23, P24-P27, and P [ 27 groups), it was showed that the short-term facilitation induced by the 5-pulse stimulations in P [ 27 group significantly weakened compared with that in P20-P23 group (F-test, P \ 0.05).…”
Section: Developmental Changes Of Stimulus-evoked Excitatory Postsynasupporting
confidence: 88%
“…The changes of the 1st eEPSC reflected the intrinsic properties of synapses including synaptic number, synaptic structure primarily, while that of the 5th eEPSC and STP preferred to embody the characters of synaptic network and mechanism of synaptic transmission, especially, based on the studies previously (Reyes and Sakmann 1999;Zucker 1989;Speed and Dobrunz 2008;Zucker and Regehr 2002), it was found that the short-term changes occur via presynaptic mechanisms primarily including the changes in neurotransmitter release and Ca 2? concentration in presynaptic terminal, etc.…”
Section: Developmental Changes Of Stimulus-evoked Excitatory Postsynamentioning
confidence: 99%
“…Several studies support the assumption of non-saturated NMDARs (Mainen et al, 1999; Mcallister and Stevens, 2000; Nimchinsky et al, 2004). In addition, the bursty firing patterns of CA3 neurons in vivo (Ranck, 1973; Suzuki and Smith, 1985; Tropp-Sneider et al, 2006; Mizuseki et al, 2009), coupled with evidence for reliable axonal propagation (Emptage et al, 1999, 2003; Meeks et al, 2005) and robust short-term synaptic facilitation at Schaffer collateral synapses (Dobrunz et al, 1997; Speed and Dobrunz, 2008), appear ideally suited to deliver the multiple glutamate releases per input “event” that can lead to strong NMDA-dependent post-synaptic responses.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, definitive elucidation of how mGlu1 receptors contribute to the neural mechanisms of associative learning is still missing. However, these effects of mGlu1 receptors may tentatively be ascribed to a modulation of GABAergic transmission involving hippocampal interneurons (Speed and Dobrunz, 2008).…”
Section: Distribution and Role Of Metabotropic Glutamate 1 Receptors mentioning
confidence: 99%